The Effects Of Science Writing Heuristic Approach To Improve Concept Understanding Of Stoichiometry And Attitude Towards Learning Chemistry Among Undergraduate Students - N. Pooranavelu, Kirupanithi (2018)
This study investigated the use of the science writing heuristic (SWH) approach on undergraduate university students’ understanding on the topic of stoichiometry in chemistry and to improve attitude on learning chemistry. SWH approach is a writing-to-learn strategy that incorporates guided inquiry and collaborative work. SWH approach was integrated and adapted in the teaching of stoichiometry in the tutorial classes. There was a total of 78 undergraduate university students participated in this study. These students were randomly assigned into experimental (N=36) and control (N=42) groups. For the experimental group (EG) the lessons on stoichiometry was instructed using SWH, while for the control group (CG) students the same lessons were instructed using more traditional teacher centred instruction. A Stoichiometry Concept Test (SCT), Test of Science-Related Attitude (TOSRA) questionnaire and semi-structured interviews were employed to collect the data. The quantitative data was analysed using independent sample t-tests. The outcome of the quantitative data indicated that there was a significant difference of the EG students understanding as compared to the CG’s understanding (t = 7.78 ; p˂0.05). The quantitative findings are supported by the qualitative findings from interviews which indicate an improvement in the students’ understanding of stoichiometry apparently from the exposure to the SWH approach.